KAJIAN HUKUM TENTANG TINDAK PIDANA KEJAHATAN TERORISME DI INDONESIA - Akhyar, Cut Fadhlan (E-Journal Widya Yustisia, 2005)
Terror is a word welknown worldwide. The negative impact of terror affects multidimensional life of people an a nation. The Legian bomb event in Bali on October 12, 2002 could be considered as Indonesia not being immune of such events. Terror became a monstrous event for the Indonesia people as well as the global society. Deliberation on terrorism requires a comprehensive understanding to describe the element, form, mode and related aspects of terrorism as well as its objective classification. On the other hand, even though terrorism is polularly known as a violation of human rights, we as a nation must have regulations interpreted through law proportionally